Efektivitas Bayam Dan Buah Bit Terhadap Kadar Hemoglobin Ibu Hamil - Pratiwi Hariyani Putri; Fildzah Karunia Putri; Syarafina Rahmawati Rahmawati (UNUSA Press, 2021)
Pregnancy is a process of growth and development in an intrauterine fetus from conception to be born (1). Pregnant women are a group that is prone to nutritional problems due to an increase in body metabolism resulting in an increase in the need for nutrients. One of the nutrients needed is iron and folic acid found in spinach and beets. This study aims to measure the effectiveness of spinach and beets on hemoglobin levels of pregnant women through a systematic literature review approach. The results of a review of studies related to the effectiveness of spinach on hemoglobin levels of pregnant women with varying amounts and times. This method is effective for increasing hemoglobin levels in pregnant women in addition to offering Fe tablets. Giving beets, both in the form of juice, extract / supplement is also effective in increasing hemoglobin levels for pregnant women. Based on the results of a systematic literature review in total it can be denied that spinach and beets can effectively increase hemoglobin levels for pregnant women with a minimum duration of administration for 7 days in various types of preparations.